2019
DOI: 10.25165/j.ijabe.20191203.4868
|View full text |Cite
|
Sign up to set email alerts
|

Influence of UAV flight speed on droplet deposition characteristics with the application of infrared thermal imaging

Abstract: A plant protection unmanned aerial vehicle (UAV) applied for spraying pesticide has the advantages of low cost, high efficiency and environmental protection. However, the complex and changeable farmland environment is not conductive to perform spray test effectively. It is therefore necessary to carry out spray test under controlled conditions. The current study aimed to illuminate the variation law of droplet deposition characteristics under different UAV flight speeds, and to verify the feasibility for apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
(21 reference statements)
2
14
0
Order By: Relevance
“…p−values are all less than 0.05). Overall speaking, the increase of flight velocity will significantly decrease the droplet coverage rate, which actually meets our expectation and is also consistent with previous results [13,14]. (2) for inter-row route, "spraying once" has a higher droplet coverage value over "spraying twice" at all tested positions.…”
Section: Effects Of Flight Velocitysupporting
confidence: 93%
See 1 more Smart Citation
“…p−values are all less than 0.05). Overall speaking, the increase of flight velocity will significantly decrease the droplet coverage rate, which actually meets our expectation and is also consistent with previous results [13,14]. (2) for inter-row route, "spraying once" has a higher droplet coverage value over "spraying twice" at all tested positions.…”
Section: Effects Of Flight Velocitysupporting
confidence: 93%
“…It is noted that most of the existing results are on cereal crops rather than orchard trees. For example, the effects of flight height and flight velocity on droplet deposition distribution were investigated in wheat [11], cotton [12] and indoor environment [13], respectively. It was shown in both crops [11] [12] that increase of flight height within a certain range (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This ensures even coverage with limited wastage. Lv et al [16] demonstrated the practicability of infrared thermal imaging in evaluating the droplet deposition in the field of aerial spraying. In the study, the effect of UAV flight speed on the spray droplets was investigated and the variable spray test was conducted by a UAV simulation platform, with airborne spray system under controllable environment.…”
Section: Crop and Spot Sprayingmentioning
confidence: 99%
“…Lv has analyzed the influence of flight speed on droplet deposition. The analysis concluded that deposition density and coverage, mean droplet size decreases with increasing speed [26]. A. S. Mat Su in his study suggests that height of 1.5 to 2.0 m from the crop is suitable for spraying over rice crop.…”
mentioning
confidence: 91%